APTES-Terminated ultrasmall and iron-doped silicon nanoparticles as X-Ray dose enhancer for radiation therapy - Klein, Stefanie; Wegmann, Marc; Distel, Luitpold; Neuhuber, Winfried; Kryschi, Carola (Biochemical and Biophysical Research Communications, 2018)
Silicon nanoparticles with sizes between were synthesized through wet-chemistry procedures using diverse phase transfer reagents. On the other hand, the preparation of iron-doped silicon nanoparticles was carried out using the precursor Na4Si4 containing 5% Fe. Biocompatibility of all silicon nanoparticle samples was achieved by surface-stabilizing with (3-aminopropyl)triethoxysilane. These surface structures provided positive surface charges which facilitated electrostatic binding to the negatively charged biological membranes. The mode of interaction with membranes, being either incorporation or just attachment, was found to depend on the nanoparticle size. The smallest silicon nanoparticles (ca. 1.5 nm) were embedded in the mitochondrial membrane in MCF-7 cells. When interacting with X-rays these silicon nanoparticles were observed to enhance the superoxide formation upon depolarizing the mitochondrial membrane. X-ray irradiation of MCF-7 cells loaded with the larger silicon nanoparticles was shown to increase the intracellular singlet oxygen generation. The doping of the silicon nanoparticles with iron led to additional production of hydroxyl radicals via the Fenton reaction.
EVALuna2:35202

Oxidized silicon nanoparticles for radiosensitization of cancer and tissue cells - Klein, Stefanie; Dell'Arciprete, Maria L.; Wegmann, Marc; Distel, Luitpold; Neuhuber, Winfried; Gonzalez, Monica C.; Kryschi, Carola (Biochemical and Biophysical Research Communications, 2013)
The applicability of ultrasmall uncapped and aminosilanized oxidized silicon nanoparticles (SiNPs and NH-SiNPs) as radiosensitizer was studied by internalizing these nanoparticles into human breast cancer (MCF-7) and mouse fibroblast cells (3T3) that were exposed to X-rays at a single dose of 3Gy. While SiNPs did not increase the production of reactive oxygen species (ROS) in X-ray treated cells, the NH-SiNPs significantly enhanced the ROS formation. This is due to the amino functionality as providing positive surface charges in aqueous environment. The NH-SiNPs were observed to penetrate into the mitochondrial membrane, wherein these nanoparticles provoked oxidative stress. The NH-SiNPs induced mitochondrial ROS production was confirmed by the determination of an increased malondialdehyde level as representing a gauge for the extent of membrane lipid peroxidation. X-ray exposure of NH-SiNPs incubated MCF-7 and 3T3 cells increased the ROS concentration for 180%, and 120%, respectively. Complementary cytotoxicity studies demonstrate that these silicon nanoparticles are more cytotoxic for MCF-7 than for 3T3 cells. © 2013 Elsevier Inc.